The Managing Director's Global Policy Agenda : A More Inclusive and Resilient Global Economy April 2017. (Policy Papers; Policy Paper ;, 2017)
The global economy is gaining momentum, but further progress hinges on policies to support the recovery, lift productivity growth, and enhance resilience. Against the background of rapid technological progress, a cooperative multilateral framework for trade and financial integration has served countries well, producing large economic benefits. However, some groups have not been able to share in these benefits, a trend exposed by a too-slow post-crisis recovery, which limited the room for all segments of society to experience income gains. Working within the multilateral framework, countries should strive for strong and more balanced growth and to provide economic opportunities for all. To this end, they should anticipate the effects of technological progress and economic integration, equip their populations with tools to reap the benefits, and put in place domestic policies to share them more broadly. The Fund will assist members through carefully tailored policy advice, lending to smooth adjustment, and capacity development.